Undergraduate Research Thesis: Is it really a Necessity or an Unnecessary Burden? - Martinez, Rudolf Cymorr Kirby (Journal of Health and Caring Sciences, 2019)
The prevailing tradition of requiring a completed research paper, in the form of a thesis, in most higher institute of learning in the Philippines seems to be born out of an archaic tradition rather than any educational pedagogy. This editorial provides arguments for the above mentioned assertion.